Afgrundsblikket - Det erotiske og repræsentationen hos Nietzsche og Sade - Grimm, Jon Auring (Slagmark - Tidsskrift for idéhistorie, 2018)
Erotic desire is intimately connected with the problem of representation. Since desire is directed towards the other, it becomes a problem how the other is represented and whether or not the abyss thus opened between the desiring and the desired can be overcome. Two approaches to this problem are investigated and compared: Friedrich Nietzsche’s and Marquis de Sade’s. It is claimed that while de Sade in his endless transgressions affirms the reactionary representation of the other, Nietzsche opens a possibility of a transgression of representation as such.